Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Multiply and simplify
(x-3y) (x + 3y)


Sagot :

[tex](x-3y) (x + 3y)=x^2-9y^2\\\\ (a-b)(a+b)=a^2-b^2[/tex]
[tex](x-3y)(x+3y) \\ =x^2+3xy-3xy-9y^2 \\ =x^2-9y^2[/tex]